Follicular and luteal morphometry, progesterone concentration and early gestation in Holstein cows (Bos Taurus) at high altitude in the tropics (Colombia) - Marbel Monroy G (Revista MVZ Córdoba, 2018)
Objectives. The aim of this study is to evaluate the relationship among ovulatory follicle (OF) size, corpus luteum (CL) volume, and progesterone (P4) serum levels with pregnancy success. Materials and methods. Nineteen Holstein cows located in Bogotá, Colombia with a history of 2 to 6 previous calving were used in the study. Following 40 day postpartum, two consecutive phases were evaluated as follows: 1) estrous cycle; 2) early pregnancy or return to estrus after Artificial Insemination (AI). Ultrasound exam was performed twice daily after first sign of estrus to evaluate OF diameter and CL volume, and serum P4 levels were evaluated on days 6, 9, 12 and 15 after ovulation. Cows were inseminated 12 hours post estrus signs and pregnancy was diagnosed 30 days post AI. Results. 47.36% of the cows were diagnosed as pregnant after AI. Pregnant cows had smaller OF diameters (17.85±2.39 mm) than non-pregnant females (21.10±2.86 mm) (p<0.05). Cows with smaller OF were more likely to become pregnant (OR=0.624, IC=95% (0.4-0.9) (p<0.05). There were non significant differences in the CL volume (p=0.10) and P4 serum values (p=0.39) between pregnant and no pregnant cows on days 6, 9, 12 and 15 post ovulation. Serum P4 levels were not correlated to CL size and reproductive status. Conclusions. This study shows that there was not significant difference in serum P4 levels and the CL volume when comparing pregnant with non-pregnant cows. A relationship was found between the OF diameter and the CL volume. Small OF diameter was a factor associated with early pregnancy.